An Investigation of the Altered Textural Property in Woody Breast Myopathy Using an Integrative Omics Approach - Welter, Amelia A.; Wu, Wan Jun; Maurer, Ryan; O’Quinn, Travis G.; Chao, Michael D.; Boyle, Daniel L.; Geisbrecht, Erika R.; Hartson, Steve D.; Bowker, Brian C.; Zhuang, Hong (Frontiers in Physiology, 2022)
Woody breast (WB) is a myopathy observed in broiler Pectoralis major (PM) characterized by its tough and rubbery texture with greater level of calcium content. The objective of this study was to investigate the functionality/integrity of WB sarcoplasmic reticulum (SR), which may contribute to the elevated calcium content observed in WB and other factors that may influence WB texture. Fourteen Ross line broiler PM [7 severe WB and 7 normal (N)] were selected, packaged and frozen at -20°C at 8 h postmortem from a commercial processing plant. Samples were used to measure pH, sarcomere length, proteolysis, calpain activity, collagenase activity, collagen content, collagen crosslinks density and connective tissue peak transitional temperature. Exudate was also collected from each sample to evaluate free calcium concentration. The SR fraction of the samples were separated and utilized for proteomic and lipidomic analysis. The WB PM had a higher pH, shorter sarcomeres, less % of intact troponin-T, more autolyzed μ/m calpain, more activated collagenase, more collagen content, greater mature collagen crosslinks density and higher connective tissue peak transitional temperature than the N PM (P ≤ 0.05). Exudate from WB PM had higher levels of free calcium than those from N PM (P < 0.05). Proteomics data revealed an upregulation of calcium transport proteins and a downregulation of proteins responsible for calcium release (P < 0.05) in WB SR. Interestingly, there was an upregulation of phospholipase A2 (PLA2), and cholinesterase exhibited a 7.62-fold increase in WB SR (P < 0.01). Lipidomics data revealed WB SR had less relative % of phosphatidylcholine (PC) and more lysophosphatidylcholine (LPC; P < 0.05). The results indicated that upregulation of calcium transport proteins and downregulation of calcium release proteins in WB SR may be the muscle’s attempt to regulate this proposed excessive signaling of calcium release due to multiple factors such as upregulation of PLA2 resulting in PC hydrolysis and presence of cholinesterase inhibitors in the system prolonging action potential. In addition, the textural abnormality of WB may be the combined effects of shorter sarcomere length and more collagen with greater crosslink density being deposited in the broiler PM.